2018
DOI: 10.1016/j.cels.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Coral: Clear and Customizable Visualization of Human Kinome Data

Abstract: Protein kinases represent one of the largest gene families in eukaryotes and play roles in a wide range of cell signaling processes and human diseases. Current tools for visualizing kinase data in the context of the human kinome superfamily are limited to encoding data through the addition of nodes to a low-resolution image of the kinome tree. We present Coral, a user-friendly interactive web application for visualizing both quantitative and qualitative data. Unlike previous tools, Coral can encode data in thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 17 publications
4
138
0
Order By: Relevance
“…In this perspective aPK refers to a subset of PKLs defined by fold and sequence similarity; this is distinct from the so-called “atypical protein kinases” (AKGs). These domains are typically depicted off to the side of Coral dendogram 40 and include protein kinases such as ATM and ATR as well as bromo-domains and TRIM proteins (see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective aPK refers to a subset of PKLs defined by fold and sequence similarity; this is distinct from the so-called “atypical protein kinases” (AKGs). These domains are typically depicted off to the side of Coral dendogram 40 and include protein kinases such as ATM and ATR as well as bromo-domains and TRIM proteins (see below).…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis that follows we use this recomputed dark kinase list as the “dark kinome”. When the distribution of dark kinases is viewed using the standard Coral kinase dendrogram 40 , a remarkably even distribution is observed across subfamilies, with the exception that only eight tyrosine kinases are judged to be understudied ( Figure 3 ). In many cases light and dark kinases are intermingled on the dendrogram (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…We found that 25 kinases that were profiled at Eurofins exhibited an IC50 < 150 nM, where 239 8 kinases had IC50 ≤ 10nM (Fig. 6) 6,21 . Importantly, 6 kinases with an IC50 < 100 nM are IDG dark 240 kinases (RIOK3, also dark, was not tested at Eurofins).…”
mentioning
confidence: 79%
“…For every phosphorylated protein site, the functional score (Fig 5a), sift scores of alanine mutant (Fig 5b), the average sift scores of all variants, protein domains (Fig 4c), and kinase substrate motifs (Fig 5d) were retrieved from the previous report 11 . Kinase family tree (Fig 5c) was depicted by Coral (http://phanstiel-lab.med.unc.edu/CORAL/) 58…”
Section: Bioinformatics Analysesmentioning
confidence: 99%